Quality of Macronutrient of Cow's Milk with Addition of Soybean Oil and Phycocyanin Extract as Functional Food - Nefasa, Angela Nitia; Wulandari, Eudia Christina; Christwardana, Marcelinus; Hadiyanto, H. (Food Science and Technology Journal (Foodscitech), 2020)
The purpose of this study was to determine the further effect of soybean oil and phycocyanin extract against the quality of macronutrient (fat, protein, lactose) and also Solid Non-Fat (SNF) in cow’s milk. Two different substances, i.e., soybean oil and different amount of phycocyanin extract was added into the milk. The result showed the increase of protein content gradually from 3.49 ± 0.230 to 3.88 ± 0.010 when phycocyanin was added. The inverse with the decreased fat content from the control sample, but after the addition of phycocyanin extract, it was increased gradually 6.15 ± 0.210 to 6.35 ± 0.21. SNF has increased from 10.61 ± 0.014 to 10.87 ± 0.007, while the decreasing level of lactose has been shown from 5.74  ± 0.021 to 5.62  ± 0.028 due to addition of phycocyanin. In conclusion,  the addition of phycocyanin extract can increase the protein and SNF content of milk. This phycocyanin extract also acts as an antioxidant agent so that it can reduce the oxidation process, which might be caused by the addition of soybean oil. Soybean oil might be used as a food additive to improve the fat content of milk but must be accompanied by an antioxidant agent to prevent the oxidation process.